2014
DOI: 10.1007/978-3-319-08599-9_28
|View full text |Cite
|
Sign up to set email alerts
|

Applying Small-Keyboard Computer Control to the Real World

Abstract: Abstract. This paper presents a usability study for text entry with a new version of the assistive keyboard replacement OnScreenDualScribe. Over five sessions (approximately 1 hr/session), three able-bodied novice participants achieved an entry rate of 13.9 wpm. In a case study, one disabled expert achieved an entry rate of 6.6 wpm. The main aspects of the software are described and differences to the ancestor DualScribe are highlighted. Finally, the potential impact of the system for persons with neuromuscula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The tool is practically usable and he does not need any other input device any more. A recent experiment with version 2.0 [3] showed that practicing with the tool makes him faster and faster. This effect, which further emphasizes the tool's practical usability, is summarized in Table 1.…”
Section: "Real-world" Usementioning
confidence: 97%
“…The tool is practically usable and he does not need any other input device any more. A recent experiment with version 2.0 [3] showed that practicing with the tool makes him faster and faster. This effect, which further emphasizes the tool's practical usability, is summarized in Table 1.…”
Section: "Real-world" Usementioning
confidence: 97%